THE IMPORTANCE OF NATIONAL AND PERSONAL VALUES IN BUILDING CIVIL SOCIETY IN NEW UZBEKISTAN - Zarina Urolovna Shamanova (Western European Studies, 2025)
This article examines the crucial role of national and personal values in the formation of civil society in New Uzbekistan. It highlights how deeply rooted cultural traditions, ethical principles, and individual responsibility contribute to fostering social cohesion, civic engagement, and sustainable development. The study also discusses the integration of these values within modern governance frameworks and educational systems, emphasizing their significance in strengthening democratic institutions and promoting social harmony in Uzbekistan’s ongoing transformation
Keywords: Civil society; national values; personal values